Development of novel proton exchange membranes and anode catalysts for fuel cells - Lu, Jin Lin (2011)
The depletion of fossil fuel and environmental pollution have led to an urgent demand for alternative energy sources and more efficient energy conversion methods. Fuel cells are a kind of electrochemical devices that can convert the chemical energy of fuels to electrical energy directly. The advantages of the fuel cell technologies are their high energy utilization efficiency and very low pollutant emissions. Proton exchange membrane fuel cell (PEMFC) is one of the most promising clean energy technologies under development in fuel cell families. Direct methanol fuel cell (DMFC) is a special form of low temperature fuel cells based on PEMFC technology. PEMFC and DMFC are extremely attractive for use in future transportation and portable electronic devices. However, there are still several major obstacles limiting their widespread commercialization and application. E.g., the production, storage and distribution of hydrogen are still the major limitations for the development of PEMFC. CO poisoning to the catalysts remains a serious problem for PEMFC and DMFC. The sluggish anode reaction of methanol oxidation and the methanol crossover causing a mixed potential reduction significantly retard the commercialization process of DMFC. If PEMFC and DMFC were operated at higher temperatures, many problems could be simplified and solved. Proton exchange membrane (PEM) is one of the most important components in PEMFC and DMFC. Dupont’s perfluorosulfonic acid (PFSA) polymer membranes (Nafion®) are the most widely used PEM owing to their high proton conductivity, good thermal and chemical stabilities. However, their proton conductivity is critically dependent on the humidity and water content in the membrane structure. So it is a challenge to develop PEMs for the operation at high temperatures and low humidity conditions. In this thesis, a novel proton-conducting inorganic membrane based on self-assembled phosphotungstic acid/meso-silica (HPW/meso-silica) has been developed for the high temperature operation of DMFC. The principle of the self-assembly was discussed and the properties of the HPW/meso-silica inorganic membranes were investigated in detail.